EDUKASI AKTIVITAS TIDUR DAN PRAKTIK BERCERITA (STORY TELLING) DI DESA ENSAID PANJANG SINTANG - Shinta Widiastuty Anggerainy; Mohamad Ikhsan; Siti Nurul Huda (Universitas Muhammadiyah Klaten, 2023)
Reading story or story telling is one of the positive routine activuty that is recomended for children because it can calm and increase the effecct of the duration of children sleep. For fullfil rest and sleep to improve sleep quality child and to growth and development, education sleep activity and practice story telling is needed. The aims of this community service is increase mothers’ knowledge about the importance of education sleep activuty and skill story telling practice. The activuty begins with educatioan sleep activuties that can improve the quality of children sleep and the story telling training. The training was carried out three times with lectures and aload reading technique, aloud reading exercice, and aloud reading practice. Feedback on the practice of aloud reading,and strengthening of reading houses. The results of this community service activity show that from the aspect of knowledge and attitudes, community already have knowledge about sleep activities and the role of story telling in improve sleep quality children. From the skill aspect, some of mothers were already sklii and had the ability to practice story telling and some mother stillneeded to do alot of practice to improve their ability to practice story telling. A whats App Group for Mothers Like Telling Stories has been formed as a solution and media for mothers and the team of community service to communicate aboot sleep avtivities and story telling practice. There is a need to refresh the reading house by providing new books and administrative staff for the reading house in Ensaid Panjang Village who can support and improve mother’s skill in story telling practice.